IMPACT OF EXTERNAL ACOUSTIC NOISE ON WORK PRODUCTIVITY IN MODERN RECORDING STUDIOS AND MITIGATION STRATEGIES (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This comprehensive research paper explores the multifaceted challenges posed by external ambient noise in modern sound recording environments, specifically focusing on the urban infrastructure of Nukus, Uzbekistan. The study investigates how unpredictable acoustic interference, such as high-decibel car horns and heavy traffic noise, degrades not only the technical fidelity of the recorded audio signal but also the psychological focus and creative flow of sound engineers and performers. By analyzing empirical data collected from a studio located within the Nukus Branch of the Uzbekistan State Institute of Arts and Culture, this paper proposes a multi-layered mitigation strategy. This strategy involves strategic transducer selection, temporal workflow management, and physical soundproofing techniques. The findings emphasize that environmental control is as crucial as technical hardware in the professional recording chain.
Keywords: Sound engineering, acoustic isolation, SNR, urban noise pollution, dynamic microphones, psychoacoustics, Nukus Branch of UzSIAC, workflow optimization.